STUDI KOMPARASI TEKANAN DARAH SEBELUM DAN SESUDAH TERPAPAR KEBISINGAN PADA TENAGA KERJA DI PT. ARTO METAL INTERNASIONAL SIDOARJO TAHUN 2012 - Nabilah Zahidah; Siti Surasri; Hadi Suryono (Poltekkes Kemenkes Surabaya, 2013)
PT Arto Metal International is one of the companies that utilize production machineries capable ofproducing high-intensity noise. Among the impacts of such engines relate to various health problemsamong workers who work around noisy places such as increased blood pressure. Therefore it isconsidered necessary to learn the differences in blood pressure before and after exposure to occupationalnoise upon workers of the company.This research employed analytical approach, to study the dynamics between risk factors (exposureto noise) and effect (increased blood pressure), based on time. This is a cross-sectional study, since thevariables of risk factors and effects were observed simultaneously. Sampling is done by simple randomsampling, and data were analyzed for blood pressure before and after noise exposure, by way of Paired Ttests.Measurement of noise intensity results in an average of 94.9 dBA. This noise intensity exceeds theTLV (Threshold Limit Value) as designated by the Ministry Manpower No. 51/Men/1999 which is set at 85dBA for 8 hours/day or 40 hours/week. Results of the Paired T-tests, both for systolic and diastolic bloodpressure difference between blood pressure before and after exposure to noiseTherefore, it is suggested that the company execute noise control in technical, administrativeaspects, and provided a number of ear protective devices so that every worker will wear ear protectorswhen workingKeywords: blood pressure; noise.